1974
DOI: 10.3171/jns.1974.41.5.0531
|View full text |Cite
|
Sign up to set email alerts
|

Cerebral circulation after head injury

Abstract: v' Measurements of cerebral blood flow (CBF), mean intraventricular pressure (MIVP), CSF acid-base status, and tests of autoregulation and CO2 reactivity of 43 patients were made at varying times after severe closed head injury. There was a distinct hyperemia or "luxury perfusion" in the acute phase of 1 to 14 days, followed by recovery to normal or below normal values. Metabolic CSF acidosis was found with hyperemia and probably reflected severe, diffuse cortical injury. Distinct regional CBF abnormalities, e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
20
0

Year Published

1977
1977
2017
2017

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 280 publications
(21 citation statements)
references
References 17 publications
(2 reference statements)
1
20
0
Order By: Relevance
“…The observed difference between positional rCBF changes in the brain-injured versus healthy cohorts is consistent with prior studies of cerebral hemodynamics that have demonstrated impaired cerebrovascular autoregulation in severely brain-injured patients [4348]. Furthermore, the variability in frontal cortical cerebrovascular responses to posture change observed in the brain-injured cohort is consistent with similarly heterogeneous results in prior studies that examined the effect of head-of-bed position on CBF.…”
Section: Discussionsupporting
confidence: 87%
“…The observed difference between positional rCBF changes in the brain-injured versus healthy cohorts is consistent with prior studies of cerebral hemodynamics that have demonstrated impaired cerebrovascular autoregulation in severely brain-injured patients [4348]. Furthermore, the variability in frontal cortical cerebrovascular responses to posture change observed in the brain-injured cohort is consistent with similarly heterogeneous results in prior studies that examined the effect of head-of-bed position on CBF.…”
Section: Discussionsupporting
confidence: 87%
“…44,45 The persistent 50% reduction in CBF is consistent with the findings from other TBI animal models, 44,46 as well as human TBI patients. 47 Bouma et al reported CBF values of <25 mL/min/100 g in adult patients with severe TBI within the first few hours of hospital admission, while normal CBF in adult humans is 45–50 mL/min/100 g. 48 A 40–50% CBF reduction persisting for at least 4 h has been reported in rats following fluid percussion injury (FPI). 46 FPI in neonatal piglets has been shown by Ref.…”
Section: Discussionmentioning
confidence: 99%
“…Conversely, when CPP is above the upper limit, passive vasodilation occurs. Using measures of CBF including intra-arterial xenon clearance (38) and TCD FV of the MCA (39), it has been demonstrated that disordered cerebral autoregulation occurs after severe TBI and is associated with worse outcome.…”
Section: Concepts and Historical Perspectivementioning
confidence: 99%